Relationship Between Temperature and Humidity on Rainfall: A Multiple Linear Regression Analysis - Purnama, Mohammad Dian; Mustafidah, Mutia Eva (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
Indonesia is one of the tropical countries in the world that has two seasons, the dry season and the rainy season. One of the biggest challenges in tropical countries is flooding caused by heavy rainfall. Not only does it cause flooding, rainfall also affects several sectors especially agriculture. Areas that have a lot of rain-fed agricultural land, especially rice fields, depend on rainfall because it determines crop yields. This study uses data from 12 sub-districts in Mojokerto district where agricultural activities are one of the pillars of the economy in the region. There are various factors associated with rainfall such as temperature and humidity. The data used is the year 2022 using multiple linear regression. Based on the results of the study, both predictor variables have a strong and positive relationship with rainfall with a correlation coefficient of 0.760007. With a significance level of 5% or 0.05, in the partial test, only the humidity variable has a significant effect on the amount of rainfall. While in the simultaneous test, both variables have a significant effect. These factors together have a coefficient of determination of 0.57761 or the contribution of the influence of the two predictor variables of 57.761% while the remaining 42.239% by other variables.